2482. Impact of a Recombinant Zoster Vaccine on Quality of Life: Data from a Randomized, Placebo-Controlled, Phase 3 Trial in Adult Hematopoietic Stem Cell Transplant Recipients. (26th November 2018) - Curran, Desmond; Anagnostopoulos, Achilles; Barista, Ibrahim; Bastidas, Adriana; Chandrasekar, Pranatharthi; Dickinson, Michael; Heras, Inmaculada; El Idrissi, Mohamed; Matthews, Sean; Milliken, Samuel; Coll, Jorge Monserrat; Matilla, Maria Belen Navarro; et al.
Abstract: Background: Herpes zoster (HZ) and its complications can have a substantial impact on patients' quality of life (QoL), particularly in immunocompromised patients. The vaccine efficacy (VE) of an adjuvanted recombinant zoster vaccine (RZV) was studied in a randomized, placebo-controlled, phase 3 study in adult hematopoietic stem cell transplant (HSCT) recipients (NCT01610414). The VE in preventing HZ cases was 68.2% (95% CI: 55.6%–77.5%). Herein we report the impact of the vaccine on patients' quality of life (QoL) associated with HZ episodes. Methods: HSCT recipients were randomized 1:1 to receive 2 doses of RZV or placebo, given 1–2 months apart and followed for the occurrence of HZ. QoL parameters were measured by the Short-Form health survey (SF-36) and Euro-Quality of Life-5 Dimension (EQ-5D) at baseline, 1 month and 1 year post-dose 2, as well as during suspected HZ episodes in conjunction with the Zoster Brief Pain Inventory (ZBPI). For confirmed HZ cases, QoL scores were compared between the vaccine and placebo groups. The RZV impact in reducing the ZBPI Burden of Illness and Burden of Interference scores was estimated in patients in the modified total vaccinated cohort (mTVC). The 2 scores were calculated from the area under the curve (Days 0 to 182) of the ZBPI Worst Pain and ZBPI Activities of Daily Living scores, respectively, assuming a score of 0 for patients who did not have a confirmed HZ episode. Results: Both the ZBPI maximum Worst Pain and Average Pain scores were significantly lower in the vaccine than placebo group (Table 1), suggesting less burden in breakthrough HZ cases following RZV. Consequently, the HZ Burden of Illness and Burden of Interference VE estimates were higher than the HZ VE estimate. RZV showed statistically significantly better QoL scores than placebo one week following rash-onset among patients with confirmed HZ, i.e., SF-36 bodily pain, social functioning, role emotional, mental health and mental component scores, and the EQ-5D Utility Score. Conclusion: In addition to reducing the risk of HZ and HZ complications, RZV significantly reduces the impact of HZ on patient's QoL in those who develop breakthrough disease. Funding: GlaxoSmithKline Biologicals SA. Disclosures: D. Curran, GlaxoSmithKline: Employee, GSK Shares and Salary. A. Bastidas, GSK: Employee, Salary. M. El Idrissi, GSK: Employee and Shareholder, Salary. S. Matthews, GSK group of companies: Consultant, Consulting fee. L. Oostvogels, GSK group of companies: Employee, Salary and stock and stock option. J. A. Young, GSK: Investigator, The University of Minnesota is reimbursed for contract costs associated with conducting clinical trials of vaccine. I receive no personal financial benefit.